Preparation process of copper-based catalyst

By optimizing the preparation process, the particle size uniformity and dispersibility of copper-based catalysts were improved, solving the problem of easy agglomeration of copper-based catalysts, achieving efficient carbon dioxide capture and conversion, and reducing costs.

CN121016759APending Publication Date: 2025-11-28SUZHOU YUEGONG GOLD POWDER CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511170535.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing copper-based catalysts suffer from uneven particle size and easy agglomeration in carbon dioxide capture and conversion, resulting in low conversion efficiency and high cost, making it difficult to mass-produce them on a large scale.

Method used

C4H3AlO5 was prepared using transbutyric acid, NaOH, and Al2(SO4)3·18H2O. Combined with Mg or Ni elements, aluminum-based crystals were prepared via a hydrothermal method, followed by calcination, annealing, and carbon film encapsulation to form nanoscale CuO/MgAl2O4 or CuO/NiAl2O4 catalysts. Gradient heating was used to control the grain distribution.

Benefits of technology

A copper-based catalyst with uniform grain size and large specific surface area was prepared, which improved the carbon dioxide capture and conversion efficiency, reduced the cost, and enhanced the stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016759A_ABST
    Figure CN121016759A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of a copper-based catalyst, and belongs to the field of catalysts for environmental remediation, and the preparation process comprises the following steps: 1) preparing a crystallized substance C4H3AlO5; (2) preparing an aluminum-based crystallized substance MgAl2O4 or NiAl2O4; 3) dipping the aluminum-based crystallized substance MgAl2O4 or NiAl2O4 in the copper salt solution to obtain a precursor solution, and drying to obtain precursor powder; (4) preparing a CuO / MgAl2O4 catalyst or a CuO / NiAl2O4 catalyst; and (5) the CuO / MgAl2O4 or CuO / NiAl2O4 catalyst is subjected to an annealing reaction, and the CuO / MgAl2O4 or CuO / NiAl2O4 catalyst with the nanoscale size is obtained. According to the method, trans-butanedioic acid, NaOH and aluminum salt are selected to prepare C4H3AlO5, Mg / Ni elements are added, the C4H3AlO5 and subsequent copper salt jointly form a catalyst system, the composite copper-based catalyst is generated, the preparation process is simple and stable in procedure, and the grain size is in the nanometer level; through the annealing reaction, the crystal grain agglomeration phenomenon is effectively improved; a carbon film packaging process is added, so that the stability of the catalyst is greatly enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a preparation process for a copper-based catalyst, specifically to the field of catalysts for environmental remediation. Background Technology

[0002] Against the backdrop of global warming, carbon dioxide capture, utilization, and storage (CCUS) is a key means of emission reduction. Among them, the hydrogenation of carbon dioxide to methanol has dual value: it realizes carbon recycling and can produce hydrogen from renewable energy sources (solar, wind, etc.) and store hydrogen in the form of methanol, thus taking into account both environmental protection and energy storage needs.

[0003] However, carbon dioxide molecules are stable, difficult to activate, and the reaction is limited by thermodynamic equilibrium. Conversion rates are low at low temperatures, and byproducts (such as CO) are easily generated at high temperatures. Currently, mainstream catalysts such as Pt, Pd, and Au are expensive to process and cannot be mass-produced. Copper-based catalysts for carbon dioxide capture and conversion have become a hot research topic in recent years, including copper powder, porous carbon, metal oxides, non-metal oxides, and metal-organic frameworks. Among these, metal-organic frameworks, as emerging porous crystalline materials, exhibit advantages such as high specific surface area, tunable pore size, and low density, making them highly suitable as catalyst supports and possessing strong market value. However, morphology control and particle size management remain key challenges in metal-organic framework copper-based catalysts. Therefore, how to develop a copper-based catalyst with uniform particle size, large specific surface area, and avoidance of agglomeration for efficient carbon dioxide capture and conversion is an urgent technical problem to be solved. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a preparation process for a copper-based catalyst, aiming to solve defects such as large catalyst particle size, uneven dispersion, and easy agglomeration, thereby addressing the technical problem of global warming.

[0005] A process for preparing a copper-based catalyst includes the following steps: 1) Dissolve transbutyric acid C4H4O4 in NaOH aqueous solution and gradually add it dropwise to Al2(SO4)3·18H2O aqueous solution. Stir thoroughly under hydrothermal conditions to obtain crystals. After washing, drying and activation, crystals C4H3AlO5 are obtained. 2) Grind the crystallized C4H3AlO5 from step 1) with Mg(NO3)2˙6H2O or Ni(NO3)2˙6H2O at a molar ratio of 2:1, and then sinter to obtain aluminum-based crystallized MgAl2O4 or NiAl2O4; 3) The aluminum-based crystallized compound MgAl2O4 or NiAl2O4 was impregnated in a copper salt solution to obtain a precursor solution and then dried to obtain a precursor powder; 4) The precursor powder is calcined in air to obtain CuO / MgAl2O4 catalyst or CuO / NiAl2O4 catalyst, and then cooled to room temperature in the furnace. 5) Annealing CuO / MgAl2O4 or CuO / NiAl2O4 catalysts to obtain nanoscale CuO / MgAl2O4 or CuO / NiAl2O4 catalysts.

[0006] Furthermore, it also includes a carbon film sealing process, which involves covering CuO / MgAl2O4 or CuO / NiAl2O4 catalysts with a carbon film.

[0007] Furthermore, the molar ratio of C4H4O4 to NaOH is (0.5-0.7):1, and the molar concentration of the Al2(SO4)3.18H2O solution is 0.2-0.4 mol / L.

[0008] Furthermore, in step 1), the heating temperature of the hydrothermal conditions is 65-75℃.

[0009] Furthermore, in step 1), the drying temperature is 100-120℃, the activation condition is 125-135℃, the sintering temperature is 600-700℃, and the sintering time is 11-14h.

[0010] Furthermore, the copper salt in step 3) is copper nitrate.

[0011] Furthermore, the drying conditions in step 3) are 100-120℃.

[0012] Furthermore, the calcination conditions in step 4) are a calcination temperature of 250-350℃ and a calcination time of 1.5-2.5h.

[0013] Furthermore, the annealing conditions in step 5) are gradient heating, with a heating rate of about 2℃ / min to 130-160℃, then heating at a rate not exceeding 1℃ / min to 230-270℃, holding at that temperature for 2 hours, and then cooling to room temperature with the furnace.

[0014] Furthermore, the reaction conditions for the carbon film sealing process are as follows: heating to 180-210℃ at a rate not exceeding 1℃ / min, carbonizing under a N2 atmosphere, and holding at that temperature for 2 hours.

[0015] The beneficial technical effects of this invention are: 1) In this invention, C4H3AlO5 is prepared by selecting transbutyric acid (C4H4O4), NaOH, and Al2(SO4)3.18H2O, and Mg / Ni elements are added. Together with the copper salt, they form a catalyst system to generate a composite CuO / MgAl2O4 copper-based catalyst. This preparation process is simple and stable, with a grain size at the nanoscale and a large specific surface area. 2) The present invention sets an annealing reaction for copper-based catalysts and uses a gradient heating method, especially a slow heating method in the second stage, which reduces the size of crystals and makes the crystal distribution more uniform during recrystallization of crystals, significantly improving the uniformity of crystal dispersion and effectively improving the phenomenon of crystal agglomeration. 3) The present invention also adds a carbon film encapsulation process to the copper-based catalyst material, so that the surface of the copper-based catalyst grains is covered with a carbon film, avoiding the reduction of activity caused by copper oxidation, and greatly enhancing the stability of the catalyst. Attached Figure Description

[0016] Figure 1 This is a process flow diagram of the present invention; Figure 2 These are SEM images of the copper-based catalyst from Example 1 of this invention; Figure 3 This is a SEM image of the copper-based catalyst of Example 3 of the present invention. Detailed Implementation

[0017] In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0018] Unless otherwise specified, all materials used in the embodiments of this application are commercially available.

[0019] See Figure 1-3 A process for preparing a copper-based catalyst includes the following steps: 1) Dissolve transbutyric acid C4H4O4 in NaOH aqueous solution and gradually add it dropwise to Al2(SO4)3·18H2O aqueous solution. Stir thoroughly under hydrothermal conditions to obtain crystals. After washing, drying and activation, crystals C4H3AlO5 are obtained. 2) Grind the crystallized C4H3AlO5 from step 1) with Mg(NO3)2˙6H2O or Ni(NO3)2˙6H2O at a molar ratio of 2:1, and then sinter to obtain aluminum-based crystallized MgAl2O4 or NiAl2O4; 3) The aluminum-based crystallized compound MgAl2O4 or NiAl2O4 was impregnated in a copper salt solution to obtain a precursor solution and then dried to obtain a precursor powder; 4) The precursor powder is calcined in air to obtain CuO / MgAl2O4 catalyst or CuO / NiAl2O4 catalyst, and then cooled to room temperature in the furnace. 5) Annealing CuO / MgAl2O4 or CuO / NiAl2O4 catalysts to obtain nanoscale CuO / MgAl2O4 or CuO / NiAl2O4 catalysts.

[0020] Furthermore, it also includes a carbon film sealing process, which involves covering CuO / MgAl2O4 or CuO / NiAl2O4 catalysts with a carbon film.

[0021] The molar ratio of C4H4O4 to NaOH is (0.5-0.7):1, and the molar concentration of the Al2(SO4)3.18H2O solution is 0.2-0.4 mol / L.

[0022] The heating temperature under hydrothermal conditions is 65-75℃.

[0023] The drying temperature of the crystallized C4H3AlO5 is 100-120℃, the activation temperature is 125-135℃, the sintering temperature is 600-700℃, and the sintering time is 11-14h.

[0024] The copper salt is copper nitrate.

[0025] Furthermore, the calcination conditions are a calcination temperature of 250-350℃ and a calcination time of 1.5-2.5h.

[0026] Furthermore, the annealing conditions are gradient heating, with a heating rate of about 2℃ / min to 130-160℃, and then heating at a rate not exceeding 1℃ / min to 230-270℃, holding at that temperature for 2 hours, and then cooling to room temperature with the furnace.

[0027] Furthermore, the reaction conditions for the carbon film sealing process are as follows: heating to 180-210℃ at a rate not exceeding 1℃ / min, carbonizing under a N2 atmosphere, and holding at that temperature for 2 hours.

[0028] Furthermore, the drying conditions for the precursor are 100-120℃. Example 1

[0029] A process for preparing a copper-based catalyst includes the following steps: 1) In the first reaction vessel, 0.06 mol of fumaric acid C4H4O4 was added to 80 mL of 1.30 mol / L NaOH aqueous solution, and the solution in the first reaction vessel was heated to 70 °C. In the second reaction vessel, 0.03 mol of Al2(SO4)3·18H2O was dissolved in 100 mL of deionized water, and the solution in the second reaction vessel was heated to 70 °C. The solution in the first reaction vessel was added dropwise to the second reaction vessel, and after thorough stirring, the crystallization reaction was carried out for 1.5 h to obtain a crystal. The crystal was washed with deionized water and dried at 110 °C for 8 h to obtain a white powder. Subsequently, the white powder was kept at 130 °C under vacuum for 12 h to obtain the activated crystal C4H3AlO5. 2) The activated crystallized compound C4H3AlO5 obtained in step 1) and Mg(NO3O)2˙6H2O are ground in a crucible at a molar ratio of 2:1 until homogeneous to obtain a solid mixture. The mixture is then sintered in a calcining furnace at a sintering temperature of 650 ℃ for 4 h to obtain the aluminum-based crystallized compound MgAl2O4. 3) The aluminum-based crystal compound MgAl2O4 was impregnated in a copper salt solution to obtain a precursor solution. The copper salt solution was an aqueous solution containing Cu(NO3)2.6H2O (12wt% Cu). 4) The precursor solution was dried at 110 °C to obtain precursor powder; 5) The precursor powder was calcined in air atmosphere, with the temperature increased to 300℃ at a rate of 2℃ / min, the calcination temperature was 300℃, and the calcination time was 2 h to obtain CuO / MgAl2O4 catalyst, which was then cooled to room temperature in the furnace. 6) The CuO / MgAl2O4 catalyst was annealed at a flow rate of 80 ml / min to 100 ml / min under an argon atmosphere. The temperature was increased by gradient, from 2 °C / min to 150 °C, and then from 1 °C / min to 200 °C. The temperature was held for 2 h to obtain the CuO / MgAl2O4 catalyst, which was then cooled to room temperature in the furnace.

[0030] Example 1, based on the preparation of C4H3AlO5 using fumaric acid (C4H4O4), NaOH, and Al2(SO4)3·18H2O, further adds Mg element to form a composite CuO / MgAl2O4 catalyst with subsequent copper salts. This preparation process is simple and stable, with nanoscale grain size and large specific surface area. In addition, to improve grain uniformity, annealing is carried out in an argon atmosphere, and the gradient heating method, especially the slow heating in the second stage, reduces the grain size and makes the grain distribution more uniform during recrystallization of the crystallized material, significantly improving the grain dispersion uniformity and avoiding grain agglomeration. Example 2

[0031] The difference from Example 1 is that it also includes the following steps: 7) The CuO / MgAl2O4 catalyst was impregnated in a 10% wt sucrose solution and heated to 250°C at a rate of 1°C / min. Carbonization was carried out at 250°C by passing N2 at a flow rate of 100 ml / min and held for 2 h to finally form a CuO / MgAl2O4 catalyst with a carbon film on its surface. Then it was slowly cooled to room temperature.

[0032] In Example 2, by adding a carbon film sealing process, the surface of the CuO / MgAl2O4 catalyst grains is covered with a carbon film, which avoids the reduction of activity caused by copper oxidation and greatly enhances the stability of the CuO / MgAl2O4 catalyst. Example 3

[0033] The difference from Example 1 is that Mg(NO3O)2˙6H2O in step 2) is replaced with Ni(NO3O)2˙6H2O. Example 4

[0034] The difference from Example 3 is that it also includes the following steps: 7) The CuO / NiAl2O4 catalyst was impregnated in sucrose solution and carbonized by N2 at 250℃ for 2 hours to finally form a CuO / NiAl2O4 catalyst with a carbon film on its surface.

[0035] Comparative Example 1: The difference from Example 1 is that step 6 is not included.

[0036] Comparative Example 2: The difference from Example 3 is that step 6 is not included.

[0037] The catalytic performance test results of Examples 1-4 and Comparative Examples 1 and 2 are shown in Table 1 below: Table 1 Performance test results of copper-based catalysis catalyst Methanol yield (mmol / gh) Selectivity (%) Stability (h) Example 1 52.7 89.3 403 Example 2 55.1 94.3 502 Example 3 49.9 88.5 390 Example 4 53.2 93.2 495 Comparative Example 1 40.2 78.3 210 Comparative Example 2 38.9 72.6 205 from Figure 1 The publicly disclosed processing steps and the performance parameters of the copper-based catalysts listed in Table 1 directly demonstrate that the Cu / MiAl2O4 and Cu / NiAl2O4 catalysts exhibit excellent performance in terms of stability, selectivity, and methanol yield, and their preparation process is simple, making them highly valuable for market promotion.

[0038] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A process for the preparation of a copper-based catalyst, characterized in that, The method comprises the following steps: 1) dissolving fumaric acid C4H4O4 in NaOH aqueous solution, and gradually dropping Al2(SO4)3.18H2O aqueous solution, and stirring under hydrothermal conditions to obtain a crystalline compound, and washing, drying and activating the crystalline compound to obtain a crystalline compound C4H3AlO5; 2) grinding the crystalline compound C4H3AlO5 in step 1) with Mg(NO3)2·6H2O or Ni(NO3)2·6H2O at a molar ratio of 2:1, and sintering to obtain an aluminum-based crystalline compound MgAl2O4 or NiAl2O4; 3) immersing the aluminum-based crystalline compound MgAl2O4 or NiAl2O4 in a copper salt solution to obtain a precursor solution and drying to obtain a precursor powder; 4) calcining the precursor powder in an air atmosphere to obtain a CuO / MgAl2O4 catalyst or a CuO / NiAl2O4 catalyst, and cooling to room temperature in the furnace; 5) annealing the CuO / MgAl2O4 or CuO / NiAl2O4 catalyst to obtain a CuO / MgAl2O4 or CuO / NiAl2O4 catalyst with a nanoscale size.

2. A process for the preparation of a copper-based catalyst according to claim 1, characterized in that, A carbon film sealing process is further included, in which a carbon film is covered on the CuO / MgAl2O4 or CuO / NiAl2O4 catalyst.

3. The process for preparing a copper-based catalyst according to claim 1, characterized in that, The molar ratio of C4H4O4 to NaOH is (0.5-0.7):1, and the molar concentration of the Al2(SO4)3.18H2O solution is 0.2-0.4 mol / l.

4. The process for preparing a copper-based catalyst according to claim 2, characterized in that, The heating temperature of the hydrothermal conditions in step 1) is 65-75℃.

5. A process for the preparation of a copper-based catalyst according to claim 3 or 4, characterized in that, The drying temperature in step 1) is 100-120℃, the activation condition is 125-135℃, the sintering temperature is 600-700℃, and the sintering time is 11-14h.

6. The process for preparing a copper-based catalyst according to claim 1, characterized in that, The copper salt in step 3) is copper nitrate.

7. The process for preparing a copper-based catalyst according to claim 1, characterized in that, The drying condition in step 3) is 100-120℃.

8. A process for the preparation of a copper-based catalyst according to claim 7, characterized in that, The calcination condition in step 4) is a calcination temperature of 250-350℃ and a calcination time of 1.5-2.5h.

9. The process for preparing a copper-based catalyst according to claim 1, characterized in that, The annealing condition in step 5) is a gradient temperature rise, rising to 130-160℃ at a temperature rise rate of about 2℃ / min, then rising to 230-270℃ at a temperature rise rate of not higher than 1℃ / min, and holding for 2h, and then cooling to room temperature in the furnace.

10. The process for preparing a copper-based catalyst according to claim 1, characterized in that, The reaction condition of the carbon film sealing process is rising to 180-210℃ at a temperature rise rate of not higher than 1℃ / min, carbonizing under N2 atmosphere, and holding for 2h.

Citation Information

Patent Citations

  • Oxygen carrier granule with high stability and preparation method thereof

    CN103834455A

  • Loaded type dearsenicating agent and preparation method thereof

    CN105536689A

  • Supported copper-based catalysts for hydrogen production by methanol steam reforming as well as preparation method and application of supported copper-based catalysts

    CN112108148A

  • Method for regulating and controlling grain sizes of copper and zinc components in copper-based catalyst through cobalt modification and application

    CN120459983A